Envisioning Empowerment: Crafting a Realm of Learning for Visually Impaired Scholars in Mondeor - Van Heerden , Stefan (University of the Witwatersrand, Johannesburg, 2024)
To address the critical need for more inclusive schools in South Africa, this project focussed on designing a school for visually impaired learner in Mondeor, Johannesburg. Currently, only three of these schools exist in Gauteng, which limits the opportunity for children with visual impairment to access quality inclusive education. My proposal aimed to change this, by making education accessible to the visually impaired . According to the White Paper 6 model, children between the ages of 7 and 15 need to be in school. This project placed the building where it would likely have maximum impact in terms of assisting the communities in the chosen area. The location of the school should not dictate who can attend. Anyone who is able to enroll will be able to do so, with preference being given to the visually impaired. The research and the building design aimed to create an inclusive building and to question what an architectural design for the visually impaired would entail. The research delved into experimentation and architectural precedents. The experimentation involved a sensory analysis, during which I spent time blindfolded to get a better sense of what it is like to be blind. The outcomes of these experiments informed the design of the school. The project examined various design precedents for these types of buildings and used the human body as an important design concept. I envisioned the classrooms as the centre points or nodes of the design, similar to the core of a human body, branching out, like limbs, into the different services that the building will offer. The building design aims to engage with the community by having a percentage of its site allocated to public space. This will hopefully ensure that the public can be involved in the inner workings of the school, creating a sense of place and belonging. The building presents opportunities for prototyping a circular economy, thereby enriching the residential context. These combined concepts and ideas strengthen the connections between the research and design development for a building of this nature. I can briefly conclude that the integrated research methods did assist in creating a design proposal that places itself into the context.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; visually impaired scholars; realm of learning; SDG-4: Quality education